2020
DOI: 10.1038/s41522-020-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose, Cyc8p and Tup1p regulate biofilm formation and dispersal in wild Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae is a mainly beneficial yeast, widely used in the food industry. However, there is growing evidence of its potential pathogenicity, leading to fungemia and invasive infections. The medical impact of yeast pathogens depends on formation of biofilms: multicellular structures, protected from the environment. Cell adhesion is a prerequisite of biofilm formation. We investigated the adherence of wild and genetically modified S. cerevisiae strains, formation of solid-liquid interface biofilms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, the ability to form biofilms is affected differently by growth conditions in different yeast species/strains. For example, some natural strains of S. cerevisiae , as well as yeast strains belonging to important opportunistic pathogens such as Candida albicans , C. glabrata , C. tropicalis , C. dubliniensis , and C. parapsilosis , produce biofilms, but the conditions of biofilm formation and biofilm structure can vary considerably [27] , [28] , [29] , [30] . As with bacteria, biofilm formation is usually associated with increased virulence of the yeast pathogen.…”
Section: Model and Natural Biofilmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the ability to form biofilms is affected differently by growth conditions in different yeast species/strains. For example, some natural strains of S. cerevisiae , as well as yeast strains belonging to important opportunistic pathogens such as Candida albicans , C. glabrata , C. tropicalis , C. dubliniensis , and C. parapsilosis , produce biofilms, but the conditions of biofilm formation and biofilm structure can vary considerably [27] , [28] , [29] , [30] . As with bacteria, biofilm formation is usually associated with increased virulence of the yeast pathogen.…”
Section: Model and Natural Biofilmsmentioning
confidence: 99%
“…The same is true for target genes, where current omics-based knowledge is insufficient to distinguish functions directly related to biofilm formation from metabolic functions, whose regulation also differs in different yeasts and conditions. For example, the conditions (medium composition) used to compare the 4 yeast species of the CTG clade did not lead to biofilm formation in C. glabrata and S. cerevisiae (not belonging to the CTG clade) [28] , which form a structured biofilm under different conditions [27] , [30] , [61] .…”
Section: Model and Natural Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, glucose starvation increases biofilm formation and FLO11 expression through the cAMP–PKA and SNF1 pathways (Livas et al 2011 ; Bojsen et al 2012 ). Van Nguyen et al ( 2020 ) reported that the inhibition of biofilm formation at high glucose concentration is mediated by increased Cyc8p-mediated FLO11 repression. Zara et al ( 2010 ) suggested that biofilm formation requires an energy input provided by reduced carbon sources.…”
Section: Yeast Biofilmmentioning
confidence: 99%